Ethnopharmacological Study and Antibacterial Activities of Some Plants Used in Traditional Medicine for the Treatment of Diarrheal Diseases in Gabon - Cédric Sima Obiang; Thiery Ndong Mba; Rick Léonid Ngoua Meye Misso; Juliette Ornely Orango Bourdette; Joseph Privat Ondo; Guy Roger Ndong Atome; Louis Clément Obame Engonga; Edouard Nsi Emvo (Tehran University of Medical Sciences, 2022)
The purpose of this work was to develop ethnopharmacological and biological studies of plants used in traditional medicine for the treatment of diarrheal diseases. This study results in scientific data that validates the uses of these plants in traditional medicine. Firstly, ethnopharmacological surveys were conducted with a few traditional healers from the provinces of Estuaire, Haut Ogooué and Woleu-Ntem in Gabon. Next, ethnobotanical data such as percentage of families, species, routes of administration, methods of preparation, parts used and number of plant names were analyzed and summarized. Finally, the antibacterial activities of some plants have been evaluated by diffusion and microdilution methods. Thirty-four (34) traditional healers were interviewed. A total of 90 plant species were identified during this study. They belong to 44 families, the most represented were Leguminoseae (13.33%), Apocynaceae (7.78%), Annonaceae (5.55%), Euphorbiaceae (4.44%) and Anacardiaceae (4.44%). Trees were used more (44.44%) than shrubs (32.22%), herbaceous plants (16.67%) and lianas (6.67%). The drug administration was mainly oral (84.62%) and by the anal route. Decoction and maceration were the two most used methods of preparation. Among identified plants, twenty-seven (27) plant extracts were subjected to microbiological analyzes. Plant extracts tested were active on Gram-negative and Gram-positive bacteria. Cola nitida extracts gave the best antibacterial activity against Enterococcus faecalis 103907 CIP. This study identified 90 antidiarrheal plant species and clearly shows the antimicrobial potential of several medicinal species.